Determining the Relative Importance of Personality Traits in Influencing Software Quality and Team Productivity - Qamar, Nosheen; Malik, Ali Afzal (Computing and Informatics, 2021)
Software projects are almost always team efforts and successful projects involve well-formed and well-composed teams. Past studies have revealed that personality contributes to effective team composition and, therefore, project success. Yet despite its importance, only a couple of empirical studies have quantitatively evaluated the impact of personality on software quality and team productivity. Our previous study was an effort in this direction. In that study, we proposed a metric called Team Homogeneity Index and evaluated its impact on software quality and team productivity for two phases (implementation and testing) of the software development life cycle. This study is a continuation of our previous work. In this study, we replicate our experiment on three different phases of software development life cycle (i.e. analysis and design, implementation, and testing). We also determine the weights for all five personality traits using input from the industry and propose an improved version of Team Homogeneity Index called Weighted Team Homogeneity Index. Finally, we conduct a comparative analysis of Team Homogeneity Index and Weighted Team Homogeneity Index to determine whether weights assigned to personality traits make any difference. Our findings reveal that weights do make a difference and Weighted Team Homogeneity Index is more strongly correlated than Team Homogeneity Index for almost all of the teams, especially those composed of practitioners, in the three different phases of Software Development Life Cycle.